The moral economy of crowdfunding and the transformative capacity of fan-ancing. (February 2015) - Scott, Suzanne
Fandom and crowdfunding have both been discursively constructed as spaces in which marginalized voices can make a transformative intervention into popular culture and speak back to the media industries that produce it. Keeping this parallel in mind, this article will examine two successful moments of Kickstarter "fan-ancing, " the comic anthology Womanthology: Heroic and the Veronica Mars movie, to consider their impact on the producer/consumer relationship. Although fan-financed endeavors have the potential to be industrially and culturally transformative works, striving to effect the same change on media industries and fan cultures that a fan work might have on a media property, we need to interrogate the limits of this "transformative" intervention. Examining how these respective campaigns frame fans' financial, emotional and creative investments, this article argues that though fan-anced projects have the potential to recalibrate the moral economy between producers and fans within media culture, their transformative capacity is ultimately connected to their embrace or rejection of industrial conceptions of "fan participation."